Sumoylation, Phosphorylation, and Acetylation Fine-Tune the Turnover of Plant Immunity Components Mediated by Ubiquitination - He, Zhouqing; Huang, Tingting; Ao, Kevin; Yan, Xiaofang; Huang, Yan (Frontiers in Plant Science, 2017)
Ubiquitination-mediated protein degradation plays a crucial role in the turnover of immune proteins through rapidly altering protein levels. Specifically, the over-accumulation of immune proteins and consequent activation of immune responses in uninfected cells is prevented through degradation. Protein post-translational modifications can influence and affect ubiquitination. There is accumulating evidence that suggests sumoylation, phosphorylation and acetylation differentially affect the stability of immune-related proteins, so that control over the accumulation or degradation of proteins is fine-tuned. In this paper, we review the function and mechanism of sumoylation, phosphorylation, acetylation and ubiquitination in plant disease resistance responses, focusing on how ubiquitination reacts with sumoylation, phosphorylation and acetylation to regulate plant disease resistance signaling pathways. Future research directions are suggested in order to provide ideas for signaling pathway studies, and to advance the implementation of disease resistance proteins in economically important crops.